Hasrat Kepribadian Tokoh Utama Dalam Novel Sunyi Adalah Minuman Keras Karya Sapardi Djoko Damono: Kajian Psikoanalisis Jacques Lacan - Alfaini, Moch. Ibnu Wahid (STIKes Ibnu Sina Ajibarang, 2024)
Novels are a type of literary work in the form of prose that tells the story of the main character in it. The researcher's interest in the characters in the novel became the basis for the research by choosing the object of analysis in the novel “Sunyi adalah Minuman Keras” by Sapardi Djoko Damono. Focusing on the character's psychology as an understanding that is studied by researchers using elements of personality desires which include real, imaginary, symbolic from Jacques Lacan's psychoanalytic theory. The research method used is descriptive qualitative with stages of reading a novel, taking data according to Lacan's psychoanalytic concept (real, imaginary and symbolic), and interpreting the results of the analysis. The conclusions in the research show an understanding of the existence of personality desires in Rara which are classified into three elements with several aspects, namely real (memories and beliefs), imaginary (loving and rejection), and symbolic (delusions, desires and religious awareness).